Giving students voice as a strategy for improving teacher practice. (1st March 2011) - Ferguson, Dianne; Hanreddy, Amy; Draxton, Shawna
This study used a semi-structured interview tool with elementary students in an inclusive charter school in a western state in the United States. Students with and without disabilities were asked to comment on their participation in their classroom and their perceptions of the classroom climate in order to begin a dialogue with their teachers that would lead to more participation in decision-making. Compiled data from the interviews were shared with teachers who were then interviewed about their analysis and use of the data for making improvements to their classroom environment and approach to pedagogy. Teacher responses were analysed for trends and actions taken following the feedback. Teachers concluded that the data were helpful and committed to use the tool regularly in the future to foster ongoing conversations with their students. They used the information from their students to make changes in the classroom climate, in their own teaching practices, and in the content of what they were teaching. Implications for expanding upon the use of the tool in the future to promote greater dialogue between teachers and students are discussed.